(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Thermoplastic polymers are extensively utilized in electronics, aerospace, automobile and additive manufacturing industries due to low cost, low temperature processing and reusability. Thermoplastics of different grades and chemical structures arereadily available in the market They can be reusedand reshaped, and also can be manufactured with less weight proportion as compared to the metals and ceramics by providing same strength of material. As a result, the plastics products in the market are getting popular day by day with high demand of customized products due to inception of additive manufacturing technologies. In any case, the issue of recycling these materials is challenge due to enormous energy requirements and varying chemical composition of different polymers. There are both mechanical and financial issues that restrict the advancements in this field. The recycling process of polymers can be done by the four different ways such as primary recycling process, secondary recycling process, tertiary recycling process and quaternary recycling process which can be discussed in this systematic review with practical examples. The modifications and implementation of these polymer waste recycling techniques could help to reduce wastage and save material cost which would directly affect the economy of contemporary industries.